Advances in dynamic visual acuity test research - Chen, Ganggang; Zhang, Jin; Qiao, Qi; Zhou, Liyuan; Li, Ying; Yang, Jie; Wu, Jiaxin; Huangfu, Hui (Frontiers in Neurology, 2023)
The dynamic visual acuity test (DVAT) is a functional evaluation tool for the impairment and compensation of the vestibular system, which could reflect the Vestibulo-ocular reflex (VOR) function. We present an overview of DVAT research, displaying recent advances in test methods, application, and influencing factors; and discussing the clinical value of DVAT to provide a reference for clinical application. There are two primary types of DVAT: dynamic-object DVAT and static-object DVAT. For the latter, in addition to the traditional bedside DVAT, there are numerous other approaches, including computerized DVAT, DVAT on a treadmill, DVAT on a rotary, head thrust DVA (htDVA) and functional head impulse testing (fHIT）, gaze shift dynamic visual acuity with walking (gsDVA), translational dynamic visual acuity test(tDVAT), pediatric DVAT. The results of DAVT are affected by subject, occupation, static visual acuity (SVA), age, eyeglasses lens, testing methods, caffeine, and alcohol. DVAT has numerous clinical applications, such as screening for vestibular impairment, assessing vestibular rehabilitation, predicting fall risk evaluating ophthalmology-related disorders, vestibular disorders, and central system disorders.